The Effect of Combination Cream of Patchouli Extract and Arabica Gayo Coffee Peel Extract on Aging Skin - Lestari, Wahyu; Dewi Ismida, Fitri; Hajar, Sitti; Clarissa Namiko, Rifda (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Indonesia is a tropical country that is exposed to sunlight throughout the year. Due to this exposure, Indonesians are more susceptible to aging. It has been demonstrated that the antioxidative chemicals in Aceh nilam and Arabica Gayo coffee peel extract can prevent the aging process of the skin. Purpose: To observe the effect of combination cream patchouli extract and arabica Gayo coffee peel extract on aging skin, focusing on collagen and elastin. Methods: This is an exploratory study using a randomized post-test only design. The rats were divided into two control groups and three experimental treatments, each with a different active ingredient concentration (10%, 12.5%, and 15% of patchouli and coffee peel extract). For six weeks, each group is exposed to UVB light three times a week, for a total dose of 1020 mJ/cm2. The macroscopic morphology, density, and thickness of collagen and elastin in rat skin were observed and assessed. Result: There were noteworthy variations observed in collagen density, collagen thickness, and elastin density, whereas no significant difference was found in elastin thickness. The macroscopic skin morphology exhibited absence of inflammation across all experimental groups. Conclusions: This study suggests that cream containing Aceh patchouli extract and 15% of Arabica Gayo coffee peel extract exhibits potential in enhancing the quantity and quality of collagen while preserving elastin levels and it is safe for rat skin.